2020
DOI: 10.1055/a-1099-9556
|View full text |Cite
|
Sign up to set email alerts
|

Acute Statin Administration Reduces Levels of Steroid Hormone Precursors

Abstract: Cholesterol-lowering statin drugs are used by approximately 25% of US adults 45 years of age and older and frequency of use is even higher among the elderly. Cholesterol provides the substrate for steroid hormone synthesis and its intracellular concentrations are tightly regulated. Our aim was to evaluate whether statin use acutely changes the circulating levels of cortisol, other glucocorticoid precursor molecules and their metabolites. Fourteen subjects not taking statins were administered a single oral dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The study by Munkboel et al conducted on mouse models has shown that atorvastatin is able to influence steroid homeostasis, resulting in a down-regulation of the StAR protein and the CYP11A1 enzyme, responsible for cleavage of cholesterol chain leading to pregnenolone [ 32 ]. A recent work by London et al on 14 subjects, confirmed that multiple precursors of steroidogenesis decrease significantly 24 h after the first administration of pitavastatin, despite unsignificant plasma variation in cortisol and aldosterone levels [ 33 ]. This concern could be an intriguing topic of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Munkboel et al conducted on mouse models has shown that atorvastatin is able to influence steroid homeostasis, resulting in a down-regulation of the StAR protein and the CYP11A1 enzyme, responsible for cleavage of cholesterol chain leading to pregnenolone [ 32 ]. A recent work by London et al on 14 subjects, confirmed that multiple precursors of steroidogenesis decrease significantly 24 h after the first administration of pitavastatin, despite unsignificant plasma variation in cortisol and aldosterone levels [ 33 ]. This concern could be an intriguing topic of future research.…”
Section: Discussionmentioning
confidence: 99%
“…From a biological and physiological viewpoint, a cumulative dose-effect would rather have been expected. London et al had shown in their study of 14 patients that a single treatment with a lipophilic statin reduced the production of some glucocorticoid precursors (12). This effect could have a clinical impact but it is possible that a compensatory phenomena allow glucocorticoid synthesis to be maintained or regulated.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting cholesterol synthesis, statins could be responsible of a reduction of steroid hormones synthesis and thereby cause adrenal insufficiency (AI). Today, only a few studies concerning a limited number of patients showed contradictory results on steroid hormone synthesis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HMGCR inhibitors, statins, which are cholesterol-lowering drugs, have an impact on the treatment of depression [81]. Statins can decrease cholesterol de novo synthesis and reduce steroid hormone precursors, such as cortisone and corticosterone [82]. In addition, statins are involved in the regulation of serotonin receptor dynamics, leading to the upregulation of serotonin levels in the hippocampus [81].…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%